Pathogenicity, histological and molecular characterization of fowl adenovirus 8b propagated in eggs and chicken embryo liver cells in a bioreactor - C., Ugwu C.; Bejo, M. Hair; M. I., Nurulfiza; Omar, A.R.; I., Aini (Academic Journals, 2023)
Background and Objective: Fowl adenovirus 8b vaccine development is critical for the control of Inclusion Body Hepatitis (IBH) in chickens and scale-up for large volume production could be herculean. This study was conducted to determine the pathogenicity, histological and molecular changes of a field isolate of FAdV 8b (UPM11142) passaged in chicken embryonated eggs (CEE), chicken embryo liver (CEL) cells and propagated in microcarrier adapted CEL cells in a bioreactor. Materials and Methods: The virus isolate was inoculated into 9 days old specific pathogen-free (SPF) CEE, incubated at 37EC and monitored daily for mortality. Virus from liver homogenates of the dead embryo was passaged 5x on freshly prepared CEL cells and 1x in Cytodex 1 microcarrier adapted CEL cells in a bioreactor and TCID50 was determined. The H&E, immunoperoxidase and immunofluorescence assays were carried out. Amplification, sequence alignments and phylogenetic analysis of hexon and fibre genes were conducted. Results: There was 100% mortality of CEE. Infected CEL cells produced cytopathic effects characteristic of FAdV. The CEL cells attached and proliferated in the microcarrier beads and were used to propagate CELP5 isolate to produce CELP5B1 with improved titre. Eosinophilic intranuclear inclusion bodies, depletion of cells and FAdV in the nucleus within 48 hrs post-inoculation were observed. All isolates were 98-100% identical and clustered together with group E, serotype 8b FAdV in the same evolutionary clade. Conclusion: Propagation of FAdV isolate in CEL cells offers the promise of further research and vaccine development while successful bioreactor propagation will be helpful in vaccine scale-up, large volume production and as the model for other viruses.